Biologic monitoring and causes of failure in cycles of sterilization in dental care offices in Mexico - Patiño-Marín, Nuria; Martínez-Castañón, Gabriel A.; Zavala-Alonso, Norma V.; Medina-Solís, Carlo E.; Torres-Méndez, Fernando; Cepeda-Argüelles, Oscar (American journal of infection control, 2015)
Biologic indicator tests (BIs) are considered the most meaningful way to verify sterilization. To monitor the cycles of sterilization using BIs in dry heat sterilizers and steam autoclaves and to identify the causes of failures in the cycles of sterilization in dental offices in San Luis Potosí, México. An invitation to participate was sent to 400 dental offices, and 206 practitioners of 200 dental offices were included. A questionnaire was given to each of the participants, asking for the following information: sterilizer type, operational parameters used (eg, temperature, pressure, and length of exposure), frequency of sterilization cycles per day, use of BIs, and maintenance procedures of the sterilizer. Two hundred thirty sterilizers were monitored using BIs. The sterilizers with positive results were monitored a second and third time to identify the cause of the failure. Twenty-two percent of practitioners (n = 46) used BIs, and 17% (n = 39) of the sterilizers reported positive results (bacterial growth). The detected failures were a mistake in the procedure (eg, temperature, time, or pressure), an absence of supervision of the procedure performed by the assistant, and improper maintenance. There are opportunities to increase information on infection control, to improve the adoption of standard quality control methods for sterilization as a routine process, to improve training on proper testing, and standardize processes. •The 50% of the practitioners accepted the invitation of participate in the study.•Twenty-two percent of the practitioners (n = 46) had used BIs.•17% (n = 39) reported bacterial grown in the sterilizers of dry heat and autoclaves.•The detected failures were a mistake in the procedure, the absence of the supervision of the procedure and improper maintenance.